2021
DOI: 10.4103/jfmpc.jfmpc_1349_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity and overweight among type 2 diabetic patients in Bisha, Saudi Arabia

Abstract: Context: Obesity is a significant worldwide public health issue and one of the significant risk factors for type 2 diabetes and cardiovascular diseases. Aims: This study aims to determine the prevalence of obesity and overweight among type 2 diabetic patients, and explore the association between Body Mass Index (BMI), social demographics and time since diagnosis. Settings and Design: This study followed a cross-sectional study design in Bisha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
6
9
1
Order By: Relevance
“…The age range of 61 years and above had the highest percentage of obesity (47.2%). Our finding is consistent with another study conducted in Bisha, Saudi Arabia [ 15 ]. On the other hand, several studies stated that patients older than 60 have the least prevalence of obesity [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The age range of 61 years and above had the highest percentage of obesity (47.2%). Our finding is consistent with another study conducted in Bisha, Saudi Arabia [ 15 ]. On the other hand, several studies stated that patients older than 60 have the least prevalence of obesity [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings were observed in a study conducted in Saudi Arabia by Alshahrani et al (2021), where 57.8% of diabetic patients were obese and 27.9% were overweight [ 15 ]. However, other local studies showed less prevalence of obesity in T2DM patients, 39.9%, and 38.3% in Khobar and Jeddah, respectively [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…37 The current study concluded that age category 45-64 years significantly had a higher risk to get obese among DM subjects (a-POR=1.53; 95% CI: 1.19-1.96) than the age category ≥ 65 years, so did the age category 15-44 years which had an almost twofold odds ratio (a-POR=2.46; 95% CI: 1.83-3.33). Previous studies reported that prevalence of overweight and obesity was highest in the age category 41-60 years, 21,40 The previous studies coincided with the current study finding that revealed a high prevalence of obesity was observed in the age category ≤ 60 years. However, the current study found that the highest prevalence was in the 15-44 years group, while previous studies found the highest prevalence was in the 41-60 years group.…”
Section: Discussionsupporting
confidence: 91%
“…However, the current study found that the highest prevalence was in the 15-44 years group, while previous studies found the highest prevalence was in the 41-60 years group. 21,40 Age category on young and middle adults had a high risk to get obese among DM subjects. The younger age groups tend to be obese in this study; it can be associated with an increased prevalence of obesity in children 41 and might be related to the onset and duration of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that there is a high prevalence of obesity among patients with type 2 diabetes [ 32 , 33 , 34 , 35 ]. According to the report of Nutrition and Health Survey in Taiwan (NAHSIT), the prevalence of obesity among older adults was 22.8% in 2013–2016 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%